Validation of Caco-2/HT29-MTX model to assess the potential risk of ingested titanium dioxide nanoparticles - Rolo, Dora (2020)
The increased use of titanium dioxide nanoparticles (TiO2NPs) as a food additive demands a deep assessment of their potential risk for human health, including their abilities to cross biological barriers. In vitro models of the intestinal barrier are being increasingly used to evaluate NPs exposure risk. Most of these studies have focused on standard monoculture models of Caco-2 monolayers. However, they exhibit several limitations such as the lack of mucus layer and a low paracellular permeability. We aim to study TiO2NPs with an in vitro model of intestinal barrier using co-culture of two types of cells: absorptive Caco-2 and mucus-secreting HT29-MTX. This co-culture confers more physiological intestinal epithelium-like properties to the model, such as mucus secretion and tight junction formation, allowing a more adequate investigation of the cellular effects elicited by NPs. Due to the multiple variables and parameters playing a part when the model's complexity is increased, we characterized the robustness of this model by evaluating cell differentiation by confocal microscopy and Western blot while monitoring epithelial barrier formation, through measurement of both transepithelial resistance (TEER)and paracellular permeability (Lucifer yellow). An optimized model of the intestinal barrier will be used to better understand the uptake, adhesion and localization of TiO2NPs, both directly and after the simulation of the human digestive process using the harmonized in vitro digestion protocol. Preliminary data shows that these complex models can add valuable information to study the potential negative impacts and genotoxicity of TiO2NPs on human health.